Analisis Pengaruh Ketidakpastian Kebijakan Ekonomi Terhadap Profitabilitas Perusahaan Energi Di Kawasan Asean-5: Peran Moderasi Dari Manajemen Modal Kerja Dan Kinerja ESG - Emiliana Dyah Kartika; Irene Rini Demi Pangestuti (Faculty of Economics and Business Diponegoro University, 2025)
Economic policy uncertainty has become a major concern for the business and financial world, especially since the global financial crisis of 2008. Companies in the energy sector, which have a high dependence on regulations and policy stability, are very vulnerable to the impacts of this uncertainty. This study aims to examine how economic policy uncertainty (WUI) affects the profitability (ROA) of energy companies in the ASEAN-5, considering the moderating effects of working capital management (CCC) and ESG performance. This research also considers financial leverage as a control variable that limits the influence beyond the study.This research uses panel data from energy companies listed on the Bloomberg Terminal over the period 2018–2023. The sample was selected using the purposive sampling method, resulting in 27 company samples out of a total of 198 companies. The analysis method used is the First-Difference Generalized Method of Moments (FD-GMM) to address potential endogeneity in the research model and ensure efficient and unbiased estimation.The research results indicate that economic policy uncertainty (WUI) negatively affects ROA, suggesting that increasing economic uncertainty can suppress the profitability of energy companies in ASEAN-5. Working capital management (CCC) has a moderating role that actually strengthens the negative impact of WUI on ROA, even though CCC directly has a positive effect on ROA. ESG performance does not have a direct impact on ROA, but ESG acts as a moderating variable that can weaken the negative impact of WUI on ROA. These findings provide insights for energy company management, regulators, and investors regarding the importance of adaptation strategies to economic policy uncertainty and the role of sustainability in enhancing the financial resilience of companies.